Biodegradable polyurethane-incorporating decellularized spinal cord matrix scaffolds enhance Schwann cell reprogramming to promote peripheral nerve repair. Issue 10 (13th February 2023) - Wang, Yanchao; Lin, Jingjing; Chen, Jinlin; Liang, Ruichao; Zhang, Qiao; Li, Jiehua; Shi, Min; Li, Lei; He, Xueling; Lan, Ting; Hui, Xuhui; Tan, Hong
Abstract : Decellularized extracellular matrix (dECM) incorporating polyurethane nerve guide conduits (NGCs) are a promising strategy to replace autogenous nerve grafting for the treatment of peripheral nerve system (PNS) injury. Abstract : Decellularized extracellular matrix (dECM) nerve guide conduits (NGCs) are a promising strategy to replace autogenous nerve grafting for the treatment of peripheral nerve system (PNS) injury. However, dECM conduits with mechanical properties that match those of peripheral nerves are yet to be well developed. Herein, we developed polyurethane-based NGCs incorporating decellularized spinal cord (BWPU-DSC NGCs) to repair peripheral nerves. BWPU-DSC NGCs have an inner three-dimensional micro–nanostructure. The mechanical properties of BWPU-DSC NGCs were similar to those of polyurethane NGCs, which were proven to promote peripheral nerve regeneration. An in vitro study indicated that BWPU-DSC NGCs could boost the proliferation and growth of cell processes in Schwann and neuron-like cells. In a rat sciatic nerve transected injury model, BWPU-DSC NGCs exhibited a dramatic increase in nerve repair, similar to that obtained by the current gold standard autograft implantation at only 6 weeks post-implantation, whereas polyurethane NGCs still displayed incomplete nerve repair. Histological analysis revealed that BWPU-DSC NGCs could induce the reprogramming of Schwann cells to promote axon regeneration and remyelination. Moreover, reprogrammed Schwann cells together with BWPU-DSC NGCs had anti-inflammatory effects and altered the activation state of macrophages to M2 phenotypes to enhance PNS regeneration. In this study, we provided a strategy to prepare polyurethane-based dECM NGCs enriched with bioactive molecules to promote PNS regeneration.